HAK ASUH ANAK BAGI IBU BEKERJA: ANALISIS MAQASID AL-SYARI’AH DAN HUKUM POSITIF INDONESIA - Azfa Rasyad; Riyan Ramdani; Ahmad Maula Hadi (LPPM STAI Muhammadiyah Probolinggo, 2026)
The determination of child custody for working mothers is a critical issue in Indonesian family law, particularly given the dual roles women assume in modern society. This study examines from a normative juridical perspective how the principles of Maqasid al-Shari’ah and positive law in Indonesia regulate and respond to the determination of child custody when the mother is employed. Employing a literature review and legal analysis of relevant legislation and case studies, the findings reveal that Maqasid al-Shari’ah emphasizes the best interests and protection of the child, while Indonesian positive law provides comprehensive legal frameworks. However, practical application requires balancing maternal caregiving responsibilities with economic roles. This research recommends responsive policies and supportive implementations to harmonize working mothers' rights with optimal child custody arrangements, ensuring children’s welfare in accordance with religious and state norms.